2022
DOI: 10.3390/ma15176092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rapid Heating and Cooling Conditions on Microstructure Formation in Powder Bed Fusion of Al-Si Hypoeutectic Alloy: A Phase-Field Study

Abstract: Al alloy parts fabricated by powder bed fusion (PBF) have attracted much attention because of the degrees of freedom in both shapes and mechanical properties. We previously reported that the Si regions in Al-Si alloy that remain after the rapid remelting process in PBF act as intrinsic heterogeneous nucleation sites during the subsequent resolidification. This suggests that the Si particles are crucial for a novel grain refinement strategy. To provide guidelines for grain refinement, the effects of solidificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Their findings revealed that intermetallic compounds grew at the interface because of the diffusion of Cu from the substrate to the liquid during solidification. The abnormal microstructure formation due to the insufficient diffusion near the fusion line is also reported in the powder-bed fusion type AM process [34,35]. Moreover, research about the diffusion from the substrate during the formation of coatings or thin film has also been reported [36][37][38].…”
Section: Inhomogeneous Formation Of Ti 2 Ni Phase Under Low Beam Powe...mentioning
confidence: 83%
“…Their findings revealed that intermetallic compounds grew at the interface because of the diffusion of Cu from the substrate to the liquid during solidification. The abnormal microstructure formation due to the insufficient diffusion near the fusion line is also reported in the powder-bed fusion type AM process [34,35]. Moreover, research about the diffusion from the substrate during the formation of coatings or thin film has also been reported [36][37][38].…”
Section: Inhomogeneous Formation Of Ti 2 Ni Phase Under Low Beam Powe...mentioning
confidence: 83%
“…The latter consists of analyzing the temperature versus time (T(t)) data collected during solidification. Thermal analysis therefore makes it possible to study different phenomena and parameters that occur during the solidification process [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon significantly affects the strength of Al-Si alloys by transferring the load from the Al matrix to the hard (rigid) Si phase in the microstructure (load capacity). Casting parameters (i.e., solidification rate, element segregation), as well as the size and distribution of microstructural components in Al-Si alloys (i.e., Si particle morphology, intermetallic compounds, spacing between secondary dendrites) have a direct impact on the microstructure, mechanical properties, and behavior of the material in case of failure (or cracking) [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%